Structural and dielectric properties of relaxor Sr0.5Ba0.5Bi2Nb2O9 ceramic - Behera, B. [UNESP]; Araujo, E. B. [UNESP]; Junior, A. F. (Maney Publishing, 2010)
Sr0.5Ba0.5Bi2Nb2O9 ceramic was prepared by a conventional solid state reaction method and studied using X-ray powder diffraction and dielectric measurements. At room temperature, an orthorhombic structure was confirmed and their parameters were obtained using the Rietveld method. Dielectric properties were studied in a broad range of temperatures and frequencies. Typical relaxor behaviour was observed with strong dispersion of the complex relative dielectric permittivity. The temperature of the maximum dielectric constant T-m decreases with increasing frequency, and shifts towards higher temperature side. The activation energy E-a approximate to 0.194 +/- 0.003 eV and freezing temperature T-f approximate to 371 +/- 2 K values were found using the Vogel-Fulcher relationship. Conduction process in the material may be due to the hopping of charge carriers at low temperatures and small polarons and/or singly ionised oxygen vacancies at higher temperatures.
Keywords: Bismuth layered; Aurivillius; Relaxor